Psychological Dynamics of Individuals with Schizophrenia Disorder - Alifa Faradilla Zahra; Fitrania Maghfiroh (International Conference on Psychology and Education (ICPE), 2024)
Schizophrenia is a severe mental disorder that affects an individual's thoughts, feelings, and behavior, marked by a loss of understanding of reality and self-awareness. Schizophrenia is generally characterized by fundamental and characteristic deviations in thought and perception, as well as inappropriate or blunted affect, while clear consciousness and intellectual abilities are usually maintained, although certain cognitive decline may develop later. This study aims to explore and understand the psychological dynamics in individuals with schizophrenia. This study employed a qualitative method with a case study approach. To achieve detailed data, assessment approaches involving autoanamnesis, alloanamnesis, also review of medical records as well as observation to identify the causes and symptoms of schizophrenia disorder in the subjects. The findings indicate that SAS’s psychological dynamics show that the clients experience intense feelings of inferiority due to social inequality. A history of experiences of being bullied, failure becoming a veterinarian, also an unsupportive family environment and limited social relationships exacerbate feelings of inferiority and hinder the development of clients' social interests. In the end, client sets too high a final goal for his work to compensate for his feelings of inferiority, but this does not happen in the reality of the client's life.